2021
DOI: 10.1002/nur.22144
|View full text |Cite
|
Sign up to set email alerts
|

Nurses' assessments of horizontal collaboration in municipal health and care services for older adults: A cross‐sectional study

Abstract: Interprofessional and interorganizational collaboration is considered key to achieving high‐quality care and positive patient outcomes, but there is limited research into how nurses working in nursing homes and home care services perceive collaboration with other municipal health and care service providers and how their assessments of collaboration vary with individual characteristics and context. The objective of this study was to map variation in nurses' assessments of horizontal collaboration with core care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Based on the demographic projections for each LAG, the given structure of care categories in LAGs, and the interviews, the forecast of LTC demand is presented in Table 1 if new facilities for community care are not developed ( 4 ). A more in-depth study was later conducted in the Posavje region.…”
Section: Results Of the Case Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the demographic projections for each LAG, the given structure of care categories in LAGs, and the interviews, the forecast of LTC demand is presented in Table 1 if new facilities for community care are not developed ( 4 ). A more in-depth study was later conducted in the Posavje region.…”
Section: Results Of the Case Studiesmentioning
confidence: 99%
“…The projection of LTC demand in five LAGs given today's structure of housing and services based on the no-migration demographic projections. 4 1 At the same standard of number of nurses per population 2 Note that demand is more than 50% higher than existing capacity today in nursing homes-NHs 3 Waiting line in LAG Pri dobrih ljudeh and LAG Prlekija is registered in LAG Goričko 4 The calculations by authors based on the European population projection 2018 data -no migration scenario. 5 Estimate of demand by 2050 (number of persons) assuming the same structure of applicants: 1/4 of the care recipients in the cohort 65-79 and 3/4 among the population 80+ (based on the no migration scenario)…”
Section: The Case Study In the Posavje Regionmentioning
confidence: 99%
See 1 more Smart Citation
“…These national health reforms within healthcare services highlight health-promotion efforts, expecting the elderly to live longer in their own homes and, if needed, to receive home care services. Norwegian municipalities are obliged to provide health and care services for older adults, where institutional care, home care, and general practitioners are defined as core services (Skinner, Veenstra et al, 2020). Home care services typically consist of help for activities of daily living (ADL), for example, personal hygiene and meals, or medication administration (Ministry of Health and Care Services, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…How the healthcare services are organized is also of importance, since collaboration between different healthcare services and professionals has an impact and can affect the quality of outcomes (Skinner, Veenstra et al, 2020). Recent research has revealed a situation, as a result of the national healthcare reforms, where the decentralization of tasks from specialist health services 1 to the municipality and primary care service has led to a greater need for information exchange and collaboration between different healthcare providers within municipal health service organizations (Gautun & Syse, 2017;Skinner, Veenstra et al, 2020). To preserve the older person's need for continuity of care, better collaboration between nurses and general practitioners (GP) is needed (Skinner, Veenstra et al, 2020).…”
Section: Introductionmentioning
confidence: 99%